On the factors influencing the chiroptical response of conjugated polymer thin films. Issue 77 (9th September 2021) - Laidlaw, Beth; Eng, Julien; Wade, Jessica; Shi, Xingyuan; Salerno, Francesco; Fuchter, Matthew J.; Penfold, Thomas J.
Abstract : We study the influence of the physical and chemical structure on the chiroptical response of fluorene-based polymeric systems and reveal the significance of electric-magnetic coupling, at both short and intermediate length scales on the magnitude of the dissymmetry. Abstract : We study the influence of the physical and chemical structure on the chiroptical response of fluorene-based polymeric systems, namely poly(9, 9-dioctylfluorene) (PFO) and the donor–acceptor type copolymer poly(9, 9-dioctylfluorene- alt -benzothiadiazole) (F8BT). We reveal the significance of electric-magnetic coupling, at both short (molecular-level) and intermediate (delocalised over multiple polymer chains) length scales, on the magnitude of the dissymmetry. These findings provide a framework for the design of new materials with an enhanced chiroptical response.